Spray pirólise de filmes de óxido de zinco dopado com alumínio e estanho - Reis, Sabrina Lara dos (Universidade Federal de São Carlos, 2019)
We present a study on the structural, optical and electrical properties of ZnO doped with Al (ZnO: Al) and with Sn (ZnO: Sn) grown on glass substrates using the Spray Pyrolysis technique. The sample were grown in the temperature range of 220-300 ° C employing as precursors Zinc acetate and Aluminum and Tin chlorides. The nominal concentrations of dopants vary from 0.01 to 1.00% for samples containing Al and from 0.05 to 2.00% for samples containing Sn. The characterization in this study used techniques as X-ray Diffraction (XRD), Optical Transmittance and Absorbance, Photoluminescence (PL), I-V Curve and Electrical Capacitance. The XRD analysis indicates that our films are polycrystalline with a wurtzite structure and preferential direction along the plane (002) with no presence of secondary phases. The doping does not interfere in the optical transparency of our films in the region of the visible spectrum, with transmittance higher than 80%. Our samples´ set present the Burstein-Moss effect. We estimate an electron concentration around 1019 cm-3 for the sample doped with 0.5% of Al, which also presented a rectifier behavior when composing a Schottky contact with gold, presenting the value of 6.3 V for knee tension and estimate of density of ionized and compensated impurities of the order of 1017 cm-3. The PL data show ultraviolet emission bands corresponding to NBE and also in the visible region corresponding to defect levels. Increasing the concentration of Al and Sn, the bandgap value estimated according to the Varshni adjustment increases, approaching the theoretical value for the ZnO (3.37 eV). At 300 K, the absorbed photons have higher energies than the photons emitted in the PL for the two sets of samples, indicating a possible doping mechanism as the dopant concentration increases.
Spray pyrolysis of zinc oxide films doped with aluminum and tin
Keywords: Óxido de zinco; Óxido condutor transparente; Spray pirólise; Filmes finos dopados; Zinc oxide; Transparent conducting oxide; Spray pyrolysis; Thin films doped; CIENCIAS EXATAS E DA TERRA::FISICA